ANALISIS LINGKUNGAN EKSTERNAL DAN INTERNAL DALAM MENYUSUN STRATEGI PERUSAHAAN (Studi Perencanaan Strategi Komoditi Kelapa Sawit Pada PT. Perkebunan Nusantara III (Persero)) - Gunawan, Dedi Septiadi; Alhabsji, Taher; Rahardjo, Kusdi (FIA UB, 2015)
The purpose of this reserach was to gain corporate level strategy for PT. Perkebunan Nusantara III that lead company becoming a champ in competition and provide a sustainable growth. The object of this research is PTPN III (Persero). This type of applied researchÂ use a quantitative approach. Method survey conducted by distributing questionnaires to the respondents as the primary data. Purposively selects respondents (purposive sampling). FDGs also conducted by five men palm oil industry players to determine the weight ang rating values on EFE, IFE, CPM, and QSPM Matrix. Secondary data were obtained from the company internal documentation and other relevant data sources. This research uses STEEPLE and Porter's Five Forces Model analysis approach to analyze the company external environment. For the Internal analysis using Value Chain analysis approach (VCA) to analyze its internal resources. Research tools used for strategy analysis are: SWOT, SPACE, BCG, IE, Grand Strategy, and QSPM Matrix. The research found that the strategy for PTPN III palm industri is Product Development Strategy and Foward Integration Strategy. Recommendations policies at the operational level that supports the selected strategies, includes: changes / additions of the company capital structure, the expansion of oil palm land area, development / downstream palm oil products that provide value-added products, and bench marking as a means of preparing HR and The best technology.Â Â